Repotenciación de un proceso automatizado para el control, monitoreo y purificación de combustible PCA901 en un sistema de llenado de tanque HFO en la empresa Generadora Rocafuerte (Generoca) provincia del Guayas - Ecuador - Betancourt Sánchez, Jinsop Fernando (2019)
The main objective of this work is to repower a process for the control, monitoring and purification of PCA901 fuel in an HFO tank filling system in the company Generoca, with the purpose of contributing with a new design of control and force, to optimize the Fuel filling times as well as minimizing the risks of spillage. The information survey and its diagnosis of the possible failures of the current fuel tank filling system are performed, this allows to identify the most critical elements in an automated process. The budget for the execution of this project is established considering the costs incurred by materials and by labor. It is also recommended preventive maintenance PCA 901 board in order to prevent future failures in the elements of control and force. In the safety part the risk of fuel spillage is minimized as well as the ergonomic risk on the part of the operator is eliminated.